2021
DOI: 10.1186/s12903-021-01607-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of topical erythropoietin on non-surgical treatment of periodontitis: a preliminary study

Abstract: Background The purpose of periodontal treatments is to reduce inflammation, restore gingival health and clinical attachment level gain by controlling microbial plaque formation and other etiological factors. One of the drugs that has been tested in many areas and shown good anti-inflammatory properties is erythropoietin (EPO). We evaluated the effect of this drug on the improvement of periodontitis after the phase I treatment. Methods This study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…As presented in Figure 8I , the statistical intra-group comparison at the end of the study showed a significant reduction in the mean PD values ( p < 0.001) and this was in accordance with a previously published study (Aslroosta et al., 2021 ). This might be attributed to the decrease in bacterial bioburden as a result of the mechanical removal of plaque and calculus and the meticulous oral hygiene restricted by the patients (Aslroosta et al., 2021 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As presented in Figure 8I , the statistical intra-group comparison at the end of the study showed a significant reduction in the mean PD values ( p < 0.001) and this was in accordance with a previously published study (Aslroosta et al., 2021 ). This might be attributed to the decrease in bacterial bioburden as a result of the mechanical removal of plaque and calculus and the meticulous oral hygiene restricted by the patients (Aslroosta et al., 2021 ).…”
Section: Resultssupporting
confidence: 92%
“…As presented in Figure 8I , the statistical intra-group comparison at the end of the study showed a significant reduction in the mean PD values ( p < 0.001) and this was in accordance with a previously published study (Aslroosta et al., 2021 ). This might be attributed to the decrease in bacterial bioburden as a result of the mechanical removal of plaque and calculus and the meticulous oral hygiene restricted by the patients (Aslroosta et al., 2021 ). While the statistical inter-group comparison revealed that group 2 showed the highest statistical reduction in PD values with a mean value of 4.50 ± 0.53 at baseline reduced to 1.87 ± 0.64 at the end of the study ( p < 0.05).…”
Section: Resultssupporting
confidence: 92%
“…EPO has been learned as a multifunctional cytokine/drug for wound healing and bone regeneration, particularly in the realm of periodontology [ 54 56 ]. An avalanche of researches argued that EPO attenuated inflammation, contributed to antiapoptosis, enhanced autophagy, and promoted angiogenesis [ 13 , 18 , 57 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, between the third and fourth weeks following free gingival transplant procedures, topical EPO treatment accelerates palate wound healing [ 189 ]. Aslroosta et al published preliminary studies in 2021 demonstrating that EPO showed potential in the treatment of people with moderate to severe chronic periodontitis [ 190 ]. In a study, Wang et al discovered that Erythropoietin enhances the osteogenesis of periodontal mesenchymal stem cells from healthy and periodontitis sources [ 191 ].…”
Section: Bioactive Agents Used For Local Periodontal Regenerationmentioning
confidence: 99%